A pro-inflammatory role of lymphoid cells in acute pleurisy in rats - Bechara, G. H.; Bates, M. B.; Dunn, C. J.; Willoughby, D. A. (Karger Publishers, 1986)
The effect of viable splenic lymphoid cells and their constituents (filtrate) on carrageenan-induced acute pleurisy was investigated in rats. Suspensions of lymphoid cells administered intravenously to recipients just prior to initiation of pleurisy enhance both the volume of exudate and cell accumulation in the pleural cavity 3 h after the irritation. Similar results were observed when filtrate of disrupted lymphoid cells was injected either 30 or 5 min before the carrageenan, but not when administered 30 min afterwards. Suspensions of bone marrow cells, on the contrary, were ineffective in producing an enhancement of the parameters studied. When administered into the pleural cavity together with carrageenan, the lymphoid cell filtrate augmented the inflammatory response to the irritant. Nevertheless, it was ineffective, per se, to elicit any local change. It is suggested that lymphoid cells may play a pro-inflammatory role in the initiation of the process by enhancing both the fluid and the cellular components of inflammation.
Keywords: carrageenan; animal experiment; inflammation; lymphocytic infiltration; nonhuman; pleurisy; priority journal; rat; respiratory system; Acute Disease; Animal; Immunization, Passive; Injections; Lymphoid Tissue; Male; Pleura; Pleurisy; Rats; Rats, Inbred Strains; Support, Non-U.S. Gov't